New records of the genus Parabolopona Matsumara (Hemiptera: Cicadellidae: Deltocephalinae), with description of a new species from India - Meshram, Naresh M.; Shashank, P. R.; Srinivasa, N. (Zootaxa, 2016)
New records for the leafhopper genus Parabolopona Matsumura from India are provided with description of Parabolopona zhangi sp. nov. Materials are deposited in the National Pusa Collection, Division of Entomology, Indian Agricultural Research Institute (IARI), New Delhi, India. Morphological illustrations are provided. A checklist and key to species of the genus along with a distribution map are also provided.